Soils, Biofortification, and Human Health Under COVID-19: Challenges and Opportunities - El-Ramady, Hassan; Brevik, Eric C.; Elbasiouny, Heba; Elbehiry, Fathy; El-Henawy, Ahmed; Faizy, Salah E.-D.; Elsakhawy, Tamer; Omara, Alaa El-Dein; Amer, Megahed; Eid, Yahya (Frontiers in Soil Science, 2021)
Soil is an important source of resources required for human health and well-being. Soil is also a major environmental reservoir of pathogenic organisms. This may include viruses like the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), which through 2020 and 2021 created dramatic catastrophes worldwide as the causative agent of the coronavirus disease of 2019 (COVID-19). So, soil has both positive and negative impacts on human health. One of the major positive impacts is the transfer of nutrients from soil to plants, and from there to humans through their diet. Biofortification is able to enhance the levels of nutrients essential to human health in the crops we consume and represents a sustainable solution to address malnutrition, which in turn may strengthen the human immune system against COVID-19. This nutrient transfer works better when we have healthy soils. Therefore, soils and biofortification have important roles to play in combatting the COVID-19 pandemic. However, several questions still remain, such as what are the expected environmental impacts of COVID-19 on soil? Can SARS-CoV-2 be transmitted through soil, and under what conditions? Which soil processes and properties influence SARS-CoV-2 survival rates and times, as well as transmission? What are the specific links between soil health and COVID-19? What are the projected soil management scenarios in response to COVID-19? Questions such as these deserve more attention as the world seeks to recover from its most recent pandemic.